Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Nanoantennas embedded in zinc oxide for second harmonic generation enhancement - Volmert, Ruth; Weber, Nils; Meier, Cedrik (Journal of Applied Physics)
Plasmonic nanoantennas for visible and infrared radiation strongly improve the interaction of light with the matter on the nanoscale due to their strong near-field enhancement. In this study, we investigate a double-resonant plasmonic nanoantenna, which makes use of plasmonic field enhancement, enhanced outcoupling of second harmonic light, and resonant lattice effects. Using this design, we demonstrate how the efficiency of second harmonic generation can be increased significantly by fully embedding the nanoantennas into nonlinear dielectric material ZnO, instead of placing them on the surface. Investigating two different processes, we found that the best fabrication route is embedding the gold nanoantennas in ZnO using an MBE overgrowth process where a thin ZnO layer was deposited on nanoantennas fabricated on a ZnO substrate. In addition, second harmonic generation measurements show that the embedding leads to an enhancement compared to the emission of nanoantennas placed on the ZnO substrate surface. These promising results facilitate further research to determine the influence of the periodicity of the nanoantenna arrangement of the resulting SHG signal.

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse – OffPlas - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Stalling, Annika; Ihde, Jörg; Mayer, Bernd (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse und Vorhersage rezeptur- und zeitabhängiger Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Lokales Konzept zur Auslegung von elastischen Klebverbindungen (LoKAl) - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Philipp, Jens; Stammen, Elisabeth; Dilger, Klaus (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Aktivieren für robuste Klebprozesse - Wie lange sind plasmaaktivierte Polymeroberflächen offen? - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Ihde, Jörg; Mayer, Bernd (Plastverarbeiter)

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Ihde, Jörg; Mayer, Bernd

Analyse rezepturabhängiger und alterungsbedingter Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson

Jointly Optimal Dereverberation and Beamforming - Boeddeker, Christoph; Nakatani, Tomohiro; Kinoshita, Keisuke; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Towards a speaker diarization system for the CHiME 2020 dinner party transcription - Boeddeker, Christoph; Cord-Landwehr, Tobias; Heitkaemper, Jens; Zorila, Catalin; Hayakawa, Daichi; Li, Mohan; Liu, Min; Doddipatla, Rama; Haeb-Umbach, Reinhold (Proc. CHiME 2020 Workshop on Speech Processing in Everyday Environments)

Asteroid: The PyTorch-Based Audio Source Separation Toolkit for Researchers - Pariente, Manuel; Cornell, Samuele; Cosentino, Joris; Sivasankaran, Sunit; Tzinis, Efthymios; Heitkaemper, Jens; Olvera, Michel; Stöter, Fabian-Robert; Hu, Mathieu; Martín-Doñas, Juan M.; Ditter, David; Frank, Ariel; et al. (Interspeech 2020)
This paper describes Asteroid , the PyTorch -based audio source separation toolkit for researchers. Inspired by the most successful neural source separation systems, it provides all neural building blocks required to build such a system. To improve reproducibility, Kaldi-style recipes on common audio source separation datasets are also provided. This paper describes the software architecture of Asteroid and its most important features. By showing experimental results obtained with Asteroid ’s recipes, we show that our implementations are at least on par with most results reported in reference papers. The toolkit is publicly available at github.com/mpariente/asteroid.

Orientierungen in der digitalen Welt

Orientierungen in der digitalen Welt

Editorial: Orientierungen in der digitalen Welt - Herzig, Bardo; Klar, Tilman-Mathies; Martin, Alexander; Meister, Dorothee M. (Orientierungen in der digitalen Welt)
Mediatisierung und Digitalisierung sind zu Synonymen für gesellschaftliche Transformationsprozesse geworden, die sich in tiefgreifenden Veränderungen unserer Lebenspraxen in Alltag, Freizeit und Beruf niederschlagen. Viele technologische Entwicklungen führen auf der einen Seite zu bereichernden Formen der Lebensgestaltung und Erhöhung der Lebensqualität, auf der anderen Seite stellen sie Selbstbestimmung, Teilhabe und Autonomie aber auch grundlegend in Frage. Wenngleich zwar der Begriff Digitalisierung im engeren technischen Sinne die Überführung von analogen Erscheinungsformen in digitale Daten – also elektronisch gespeicherte Zeichen, die in programmierbaren Computern maschinell verarbeitet werden können – beschreibt, werden die damit verbundenen Transformationsprozesse in ihrer gesellschaftlichen und (medien-)pädagogischen Bedeutung erst deutlich ,wenn man die Dimensionen der Vernetzung, der zunehmenden Generierung von Daten durch aktive (eigene) Produktion oder durch sensorische Systeme und die Algorithmisierung von Prozessen, insbesondere auch im Kontext selbstlernender Systeme, in den Blick nimmt. Orientierung wird hier nicht nur in Bezug auf die technologischen Entwicklungen zu einer zunehmenden Herausforderung, sondern auch mit Blick auf die dadurch einem dynamischen und fortlaufenden Wandel unterliegenden Medienwelten.
Die stetig zunehmende Bedeutung der Digitalisierung für Individuum und Gesellschaft kann mit der Chiffre «permanent online, permanent verbunden» umsponnen werden. Mit mobilen Endgeräten – insbesondere Smartphones, die leistungsfähigen Computern in ihren Funktionalitäten in nichts nachstehen – sind wir heute zu jeder Zeit und an nahezu jedem Ort der Welt miteinander vernetzt und haben Zugriff auf eine enorme Menge von Medienangeboten. Gleichzeitig produzieren wir eine enorme Menge an Daten, die nicht nur funktionale Bedeutung haben, sondern insbesondere ökonomische und (gesellschafts-)politische. Auch das soziale Beziehungsgefüge, der Lebenswandel und Lebensstil verändern sich. Die damit verbundenen Möglichkeiten changieren zwischen Hoffnung und Sorge, Chance und Risiko, Mündigkeit und Unmündigkeit oder kurzum kann von einem durch ein einerseits-andererseits geprägten Spannungsfeld gesprochen werden.
Von der Medienpädagogik darf zurecht erwartet werden, im Strom dieser hohen Dynamik und den oftmals enorm kurzen Innovationszyklen von Entwicklungen in mindestens zweierlei Hinsicht Orientierungen zu bieten: zum einen im Hinblick auf die für eine Orientierung in der digitalen Welt notwendigen oder angemessenen individuellen und kollektiven Bildungsressourcen; zum anderen im Hinblick auf die pädagogischen Zugänge und Massnahmen zur Ermöglichung von Orientierung sowie damit verbundene Forschungen. Gleichzeitig drängt sich die Frage auf, welchen Einfluss Medienpädagogik auf die Gestaltung von zukünftigen Entwicklungen nimmt oder nehmen kann. Können angesichts der Komplexität von (digitalen) Medien bzw. der damit verbundenen technologischen Strukturen, kulturellen Praxen, ökonomischen Bedingungen und gesellschaftlichen Implikationen solche Orientierungsleistungen – die sich auf eine im Grunde nur interdisziplinär beschreib- und verstehbare digitale Welt beziehen – überhaupt von einer Medienpädagogik als genuin erziehungswissenschaftliche Disziplin eigenständig erbracht werden? Welchen Beitrag kann Medienpädagogik in dieser interdisziplinären Gemengelage leisten? Und noch grundsätzlicher könnte danach gefragt werden, was Orientierung und Gestaltungsmöglichkeiten angesichts der Unbestimmtheit von Entwicklungen eigentlich bedeuten. Ausgehend von diesen Perspektiven und Erwägungen hat die Frühjahrstagung 2019 der Sektion Medienpädagogik folgende Fragen in den Mittelpunkt gestellt:

Welche Rolle spielt die Medienpädagogik in interdisziplinären Kontexten von Mediatisierung und Digitalisierung?
Welche Rolle nimmt die Medienpädagogik bei der Gestaltung von zukünftigen Entwicklungen ein?
Welchen Beitrag kann die Medienpädagogik in innovativen Feldern, wie z.B. VR/AR oder KI leisten?
Welche Orientierungsleistungen in Erziehung und Bildung können von der Medienpädagogik erwartet werden?

Accelerating Static Call-Graph, Points-to and Data-Flow Analysis Through Persisted Summaries - Schubert, Philipp; Bodden, Eric; Hermann, Ben

Einsatzgrenzenerweiterung und Flexibilitätssteigerung von einseitig wirkenden mechanischen Fügeverfahren durch prozessintegrierte Fügeteilerwärmung für den stahlintensiven Leichtbau - Ivanjko, Martin; Meschut, Gerson (10. Fügetechnisches Gemeinschaftskolloquium)

Search Space Characterization for AxC Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (Fifth Workshop on Approximate Computing (AxC 2020))
On the circuit level, the design paradigm Approximate Computing seeks to trade off computational accuracy against a target metric, e.g., energy consumption. This trade-off is possible for many applications due to their inherent resiliency against inaccuracies. In the past, several automated approximation frameworks have been presented, which either utilize designated approximation techniques or libraries to replace approximable circuit parts with inaccurate versions. The frameworks invoke a search algorithm to iteratively explore the search space of performance degraded circuits, and validate their quality individually. In this paper, we propose to reverse this procedure. Rather than exploring the search space, we delineate the approximate parts of the search space which are guaranteed to lead to valid approximate circuits. Our methodology is supported by formal verification and independent of approximation techniques. Eventually, the user is provided with quality bounds of the individual approximable circuit parts. Consequently, our approach guarantees that any approximate circuit which implements these parts within the determined quality constraints satisfies the global quality constraints, superseding a subsequent quality verification. In our experimental results, we present the runtimes of our approach.

ReconROS: Flexible Hardware Acceleration for ROS2 Applications - Lienen, Christian; Platzner, Marco; Rinner, Bernhard (Proceedings of the 2020 International Conference on Field-Programmable Technology (FPT))

Fast Hybrid Network Algorithms for Shortest Paths in Sparse Graphs - Feldmann, Michael; Hinnenthal, Kristian; Scheideler, Christian (Proceedings of the 24th International Conference on Principles of Distributed Systems (OPODIS))
We consider the problem of computing shortest paths in hybrid networks, in which nodes can make use of different communication modes. For example, mobile phones may use ad-hoc connections via Bluetooth or Wi-Fi in addition to the cellular network to solve tasks more efficiently. Like in this case, the different communication modes may differ considerably in range, bandwidth, and flexibility. We build upon the model of Augustine et al. [SODA '20], which captures these differences by a local and a global mode. Specifically, the local edges model a fixed communication network in which $O(1)$ messages of size $O(\log n)$ can be sent over every edge in each synchronous round. The global edges form a clique, but nodes are only allowed to send and receive a total of at most $O(\log n)$ messages over global edges, which restricts the nodes to use these edges only very sparsely. We demonstrate the power of hybrid networks by presenting algorithms to compute Single-Source Shortest Paths and the diameter very efficiently in sparse graphs. Specifically, we present exact $O(\log n)$ time algorithms for cactus graphs (i.e., graphs in which each edge is contained in at most one cycle), and $3$-approximations for graphs that have at most $n + O(n^{1/3})$ edges and arboricity $O(\log n)$. For these graph classes, our algorithms provide exponentially faster solutions than the best known algorithms for general graphs in this model. Beyond shortest paths, we also provide a variety of useful tools and techniques for hybrid networks, which may be of independent interest.

Injectivity of the inverse optimal control problem for control-affine systems - Jean, Frederic; Maslovskaya, Sofya (2019 IEEE 58th Conference on Decision and Control (CDC))

Implementing Machine Learning Functions as PYNQ FPGA Overlays - Thiele, Simon

Extension and Evaluation of Python-based High-Level Synthesis Tool Flows - Jaganath, Vivek

Machine learning for human learners: opportunities, issues, tensions and threats - Webb, Mary E; Fluck, Andrew; Magenheim, Johannes; Malyn-Smith, Joyce; Waters, Juliet; Deschênes , Michelle; Zagami, Jason (Educational Technology Research and Development)

< Big Data> aus der Perspektive von Informatischer Bildung und Medienpädagogik - Magenheim, Johannes (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Data science education - Magenheim, Johannes; Schulte, Carsten (Encyclopedia of Education and Information Technologies. Cham: Springer)

Programmieren - Lehren und Lernen mit und über Medien - Schulte, Carsten; Budde, Lea; Winkelnkemper, Felix (Mobile Medien im Schulkontext)

Residual stress measurement in GFRP/steel hybrid components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)

Plasmonic metasurfaces for controlling harmonic generations - Zentgraf, Thomas; Chen, Shumei; Li, Guixin; Zhang, Shuang (Nanoantennas and Plasmonics: Modelling, design and fabrication)

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, C.; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, M.; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)

Analytische Auslegung der Schwingfestigkeit geclinchter Verbindungen - Unruh, Eduard; Hein, David; Meschut, Gerson (10. Fügetechnisches Gemeinschaftskolloquium)

Charakterisierung und Modellierung von Kerbeffekten durch Mischverbindungen in Karosseriebauteilen aus höchstfesten Stählen - Bähr, Philipp; Sommer, Silke; Unruh, Eduard; Hein, David; Meschut, Gerson

A simplified method for the evaluation of the layer compression test using one 3D digital image correlation system and considering the material anisotropy by the equibiaxial Lankford parameter - Camberg, Alan Adam; Tröster, Thomas

Predicting fracture at non-isothermal forming conditions: A temperature dependent extension of the LS-DYNA GISSMO fracture indicator framework - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas

Transient Bodies, Bodies in Transition: An Introduction - Strauß, Sara; Schäfer-Althaus, Sarah (Transient Bodies in Anglophone Literature and Culture)

Ageing (Female) Bodies and Mortality in Eighteenth-Century Poetry - Strauß, Sara (Transient Bodies in Anglophone Literature and Culture)

Visualising Memory Loss and the Politics of Representation in Contemporary Portraiture - Strauß, Sara (Journal for the Study of British Cultures)

How Private Equity can leverage downturn M&A for value creation - Sievers, Sönke; Degen, Dominik; Kim, Daniel; Kengelbach, Jens (M&A Review Europe)

What matters for organizing M&As successfully? - Sievers, Sönke; Alexander, Schmitz
How is merger and acquisition (M&A) success associated with firm internal M&A process organization? The literature thus far acknowledges that unobservable internal firm characteristics are at least as important as observable firm- and deal-specific characteristics in regard to explaining M&A success. Thus, this paper directly asks M&A experts around the globe to shed more light on this important issue. We investigate three indices, capturing the degree of M&A 1) process standardization, 2) process duration, and 3) process attention. Next, we analyze the process participation among four organizational layers, i.e., the functional involvement of the a) top management team, b) headquarters, c) business unit management, and d) business unit functions. We predict and find that all three indices are positively associated with M&A success, while process standardization and attention to deal strategy are of particular importance. Turning to the four organizational layers, a textured analysis shows that, for instance, target valuation should be performed by the headquarters functions but not by the top management team or the business unit. Overall, our findings are important to better understand unexplored M&A success drivers and provide directions for future research. Finally, our results might help practitioners adjust their M&A process organization to further improve their M&A success.
Keywords: Mergers; Acquisitions; Success; Processes; Organization

Alternative Deals Gain Traction - Sievers, Sönke; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Kashyrkin, Anton

Downturn M&A: Die Erfolgsstrategie der Stunde? - Sievers, Sönke; Degen, Dominik; Kim, Daniel; Kengelbach, Jens (M&A Review)

Can digital feedback increase employee performance and energy efficiency in firms? Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Decisions on Extending Group Membership—Evidence from a Public Good Experiment - Grund, Christian; Harbring, Christine; Thommes, Kirsten; Tilkes, Katja Rebecca (Games)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent’s group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members’ contributions with an endogenous mechanism.

A Complexity Theoretical Study of Fuzzy K-Means - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin (ACM Transactions on Algorithms)

Using Abstract Contracts for Verifying Evolving Features and Their Interactions - Knüppel, Alexander; Krüger, Stefan; Thüm, Thomas; Bubel, Richard; Krieter, Sebastian; Bodden, Eric; Schaefer, Ina (Lecture Notes in Computer Science)
Today, software systems are rarely developed monolithically, but may be composed of numerous individually developed features. Their modularization facilitates independent development and verification. While feature-based strategies to verify features in isolation have existed for years, they cannot address interactions between features. The problem with feature interactions is that they are typically unknown and may involve any subset of the features. Contrary, a family-based verification strategy captures feature interactions, but does not scale well when features evolve frequently. To the best of our knowledge, there currently exists no approach with focus on evolving features that combines both strategies and aims at eliminating their respective drawbacks. To fill this gap, we introduce Fefalution, a feature-family-based verification approach based on abstract contracts to verify evolving features and their interactions. Fefalution builds partial proofs for each evolving feature and then reuses the resulting partial proofs in verifying feature interactions, yielding a full verification of the complete software system. Moreover, to investigate whether a combination of both strategies is fruitful, we present the first empirical study for the verification of evolving features implemented by means of feature-oriented programming and by comparing Fefalution with another five family-based approaches varying in a set of optimizations. Our results indicate that partial proofs based on abstract contracts exhibit huge reuse potential, but also come with a substantial overhead for smaller evolution scenarios.

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg K.N. (Ultramicroscopy)

Characterisation of the PS-PMMA Interfaces in Microphase Separated Block Copolymer Thin Films by Analytical (S)TEM - Bürger, Julius; Kunnathully, Vinay S.; Kool, Daniel; Lindner, Jörg K. N.; Brassat, Katharina (Nanomaterials)
Block copolymer (BCP) self-assembly is a promising tool for next generation lithography as microphase separated polymer domains in thin films can act as templates for surface nanopatterning with sub-20 nm features. The replicated patterns can, however, only be as precise as their templates. Thus, the investigation of the morphology of polymer domains is of great importance. Commonly used analytical techniques (neutron scattering, scanning force microscopy) either lack spatial information or nanoscale resolution. Using advanced analytical (scanning) transmission electron microscopy ((S)TEM), we provide real space information on polymer domain morphology and interfaces between polystyrene (PS) and polymethylmethacrylate (PMMA) in cylinder- and lamellae-forming BCPs at highest resolution. This allows us to correlate the internal structure of polymer domains with line edge roughnesses, interface widths and domain sizes. STEM is employed for high-resolution imaging, electron energy loss spectroscopy and energy filtered TEM (EFTEM) spectroscopic imaging for material identification and EFTEM thickness mapping for visualisation of material densities at defects. The volume fraction of non-phase separated polymer species can be analysed by EFTEM. These methods give new insights into the morphology of polymer domains the exact knowledge of which will allow to improve pattern quality for nanolithography.

Excess noise in Al x Ga 1 − xAs/GaAs based quantum rings - Riha, Christian; Buchholz, Sven S.; Chiatti, Olivio; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (Applied Physics Letters)

Pool-Based Realtime Algorithm Configuration: A Preselection Bandit Approach - El Mesaoudi-Paul, Adil; Weiß, Dimitri; Bengs, Viktor; Hüllermeier, Eyke; Tierney, Kevin (Learning and Intelligent Optimization. LION 2020.)

Online Preselection with Context Information under the Plackett-Luce Model - El Mesaoudi-Paul, Adil; Bengs, Viktor; Hüllermeier, Eyke (arXiv:2002.04275)
We consider an extension of the contextual multi-armed bandit problem, in which, instead of selecting a single alternative (arm), a learner is supposed to make a preselection in the form of a subset of alternatives. More specifically, in each iteration, the learner is presented a set of arms and a context, both described in terms of feature vectors. The task of the learner is to preselect $k$ of these arms, among which a final choice is made in a second step. In our setup, we assume that each arm has a latent (context-dependent) utility, and that feedback on a preselection is produced according to a Plackett-Luce model. We propose the CPPL algorithm, which is inspired by the well-known UCB algorithm, and evaluate this algorithm on synthetic and real data. In particular, we consider an online algorithm selection scenario, which served as a main motivation of our problem setting. Here, an instance (which defines the context) from a certain problem class (such as SAT) can be solved by different algorithms (the arms), but only $k$ of these algorithms can actually be run.

Kollektive Veränderungsbereitschaft als zentraler Erfolgsfaktor von Digitalisierungsprozessen an Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Zeitschrift für Hochschulentwicklung)